2022
DOI: 10.3389/fpsyt.2022.828476
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Serum Uric Acid on the Brain and Cognitive Dysfunction

Abstract: Uric acid is commonly known for its bad reputation. However, it has been shown that uric acid may be actively involved in neurotoxicity and/or neuroprotection. These effects could be caused by oxidative stress or inflammatory processes localized in the central nervous system, but also by other somatic diseases or systemic conditions. Our interest was to summarize and link the current data on the possible role of uric acid in cognitive functioning. We also focused on the two putative molecular mechanisms relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 152 publications
0
28
0
2
Order By: Relevance
“…UA, as an inhibitor of specific peroxynitrite mediated reaction ( 59 ), may protect mitochondrial function and delay the progression of SCZ through this mechanism. Previous studies have confirmed that treatment can improve the level of UA to have oxygen nitrite-mediated diseases of the nervous system ( 60 ). In addition, UA has also been found to have protective effects during inflammatory processes in the central nervous system.…”
Section: Discussionmentioning
confidence: 83%
“…UA, as an inhibitor of specific peroxynitrite mediated reaction ( 59 ), may protect mitochondrial function and delay the progression of SCZ through this mechanism. Previous studies have confirmed that treatment can improve the level of UA to have oxygen nitrite-mediated diseases of the nervous system ( 60 ). In addition, UA has also been found to have protective effects during inflammatory processes in the central nervous system.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it might be that high levels of uric acid have a dual-effect, depending on the time of exposure. In this regard, uric acid may exert its protective effect during the initial stages of the elevated levels, primarily due to its antioxidative features, but following long-term exposure to these elevated levels, after the diagnosis of gout, it may induce an inflammatory reaction that damages the brain tissue [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is an antioxidant in animal models, and its mechanism for neuroprotection in AIS is multifaceted [91].…”
Section: Uric Acidmentioning
confidence: 99%